Effects of exogenous pyoverdines on Fe availability and their impacts on Mn(II) oxidation by Pseudomonas putida GB-1 - Lee, Sung-Woo; Parker, Dorothy L.; Geszvain, Kati; Tebo, Bradley M. (Frontiers in Microbiology, 2014)
Pseudomonas putida GB-1 is a Mn(II)-oxidizing bacterium that produces pyoverdine-type siderophores (PVDs), which facilitate the uptake of Fe(III) but also influence MnO2 formation. Recently, a non-ribosomal peptide synthetase mutant that does not synthesize PVD was described. Here we identified a gene encoding the PVDGB-1 (PVD produced by strain GB-1) uptake receptor (PputGB1_4082) of strain GB-1 and confirmed its function by in-frame mutagenesis. Growth and other physiological responses of these two mutants and of wild type were compared during cultivation in the presence of three chemically distinct sets of PVDs (siderotypes n°1, n°2, and n°4) derived from various pseudomonads. Under iron-limiting conditions, Fe(III) complexes of various siderotype n°1 PVDs (including PVDGB-1) allowed growth of wild type and the synthetase mutant, but not the receptor mutant, confirming that iron uptake with any tested siderotype n°1 PVD depended on PputGB1_4082. Fe(III) complexes of a siderotype n°2 PVD were not utilized by any strain and strongly induced PVD synthesis. In contrast, Fe(III) complexes of siderotype n°4 PVDs promoted the growth of all three strains and did not induce PVD synthesis by the wild type, implying these complexes were utilized for iron uptake independent of PputGB1_4082. These differing properties of the three PVD types provided a way to differentiate between effects on MnO2 formation that resulted from iron limitation and others that required participation of the PVDGB-1 receptor. Specifically, MnO2 production was inhibited by siderotype n°1 but not n°4 PVDs indicating PVD synthesis or PputGB1_4082 involvement rather than iron-limitation caused the inhibition. In contrast, iron limitation was sufficient to explain the inhibition of Mn(II) oxidation by siderotype n°2 PVDs. Collectively, our results provide insight into how competition for iron via siderophores influences growth, iron nutrition and MnO2 formation in more complex environmental systems.